PERKEMBANGAN EKSPOR NON-MIGAS INDONESIAPERIODE 2012-2016 - Muhammad Multazam; Ahmad Zafrullah TN.; Bambang Budiarto (CALYPTRA, 2018)
The purpose of this study is to analyze the development of Indonesia's non-oil / gas exports from various sectors and commodities over the period of 5 years (2012-2016) and to examine the export potential of Indonesia's sectors and commodities in the face of competition in the international market. This research uses descriptive qualitative method to improve the condition that happened about. Export of non oil and gas indonesia. The data used in the research is non-oil export data from 2012to 2016 obtained by government agencies and literature study. The result of research shows that the development of non oil and gas export in Indonesia tends to decrease. the causes of such price declines include the 2008-2009 global financial crisis, the decline in prices of major commodities in the market, and domestic shortages such as low competitiveness and growth rates. Opportunity development of non oil and gas export Indonesia can be maximized through government policies.